Simulation and Evaluate The Performance of The Pure Optical Amplifier Using a Split-Phase Fourier Transform Algorithm - Arraj, Faek; Sakkour, Afif; Essa, Hadeel; Abbas, Nagham (Latakia University Journal -Engineering Sciences Series, 2020)
Attenuation in optical communication systems is a key determinant imposed by the optical elements used or the fiber itself, which limits the performance of the optical communication system and reduces transmission distance. Therefore, optical amplifiers used in the optical system must be developed to compensate for signal attenuation and allow for very long distances. The increase in the number of channels sent in wavelength division multiplexing optical systems is also accompanied by a similar increase in the basic nonlinear effects affecting the signal transmitted across these fibers. Modern optical communications systems therefore require performance be evaluated by the presence of inhibitory determinants resulting from the fiber before its practical implementation. Any attempt to model optical fiber must take into account both the effects that occur. One method used to model the propagation of the optical fiber signal used as a Raman amplifier is based on Schrodinger’s non-linear equation solution. The method of solving this is called a Split Step Fast Fourier Transform, which takes into account the fundamental factors affecting the optical signal transmitted through this amplifier. Using the MATLAB simulation program, this amplifier’s performance was compared for different types of pumping and for different values of the design parameters and performance evaluation through the BER error rate and factor Q. يعد التخميد في نظم الاتصالات الضوئية عامل محدد أساسي يفرض من قبل العناصر الضوئية المستخدمة أو من قبل الليف الضوئي نفسه، فيحد من أداء نظام الاتصالات الضوئية ويقلل مسافة الإرسال. لذا لابد من تطوير المضخمات الضوئية المستخدمة في النظام الضوئي لتعويض تخميد الاشارة والسماح بالإرسال للمسافات الطويلة. كما يترافق التزايد الكبير في عدد القنوات المرسلة في الأنظمة الضوئية، المستخدمة لتقنيات التجميع بتقسيم طول الموجة لزيادة سعة الارسال، مع تزايد مماثل في التأثيرات اللاخطية الأساسية المؤثرة في الإشارة المنتشرة عبر هذه الألياف، لذا تتطلب أنظمة الاتصالات الضوئية الحديثة تقييم الأداء بوجود المحددات المعيقة الناتجة عن الليف قبل تنفيذه عملياً. أي محاولة لنمذجة الليف الضوئي يجب أن تأخذ بالحسبان كلاًّ من التأثيرات التي تحدث. وإحدى الطرق المتبعة لنمذجة انتشار الإشارة عبر الليف الضوئي المستخدم كمضخم رامان الضوئي تعتمد على حل معادلة شرودنغر غير الخطية، وتدعى طريقة حلها بتحويل فورييه السريع ذي الخطوة المجزأة، التي تأخذ بالحسبان العوامل الأساسية المؤثرة في الإشارة الضوئية المرسلة عبر هذا المضخم. باستخدام برنامج المحاكاة MATLAB، تم من خلال هذا البحث مقارنة أداء هذا المضخم من اجل طرق ضخ مختلفة ومن اجل قيم مختلفة للبارامترات التصميمية وتقييم أدائه من خلال معدل خطأ البت BER والعامل Q.